Importance of Feeding to an Infant - Rai (Shrestha), Janaki (Journal of Nursing Education of Nepal, 2011)
Breastfeeding is the ideal form of infant feeding and is crucial for lifelong health and well-being. It provides unique nutritional, immunological, psychological and child spacing benefits.  Artificial feeding exposes the infant to infection which can lead to mortality. Breastfeeding is natural and physiological and has numerous benefits to mother and child. The current infant feeding practices are far from optimum because of a lack of knowledge and training in others, misconceptions in the communities, misinformation by infant food manufacturers, and lack of community and family support. In Nepal, the infant mortality rate is 48/1000 live births and each year in Nepal, more than 50,000 children die and malnutrition is the underlying cause that accounts for 60% of these deaths. Effective breastfeeding alone can reduce 16% of Nepal’s child mortality (UNICEF/NDHS 2006).World Health Organization had emphasized the value of breastfeeding for mothers as well as children. This organization had recommended exclusive breastfeeding for the first six months of life and then supplemented breastfeeding for at least one year and up to two years or more. Therefore, every mother is responsible for her child’s health and should know the benefit of own breastfeeding rather than artificial feeding and she should have enough support by family and community to bring it into practice.
Keywords: N/A